Isolation and cloning of ABCA2 gene from rasbora sarawakensis - Tan, Say Yen. (Universiti Malaysia Sarawak, (UNIMAS), 2015)
ABC genes encode ABC transporter protein that plays an important role in ATP hydrolysis in which to assist the solute to cross the plasma membrane. Mutation of ABC genes lead to human diseases such as Alzheimer, PFIC, and PXE. The aim of this research is to identify the expression of ABCA2 gene in Rasbora sarawakensis and subsequently clone into pGEM-T® Easy vector. Total RNA was initially isolated from whole fish homogenate using Tri reagent and phenol chloroform precipitation.